1969
DOI: 10.1099/00221287-56-2-171
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation in Bacillus subtilis. Establishment of a Time Scale for the Morphological Events

Abstract: S U M M A R YChemostat cultures of Bacillus subtilis can be obtained in which a large proportion of the cells are initiated to sporulation. In a steady-state culture the fraction of cells which exhibit any particular stage of spore development is a function of the time taken for a cell to reach that stage after having been initiated to spore formation, and oft he time required for the cell to pass through that stage. Equations describing this relationship have been derived. From these equations and from values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 7 publications
(2 reference statements)
2
20
0
Order By: Relevance
“…3A). Engulfment was completed (stage III) within 60 to 90 min of septation, similar to times reported previously for B. subtilis (12,32). The strain containing the 2.3-Mb insert, SL14378, appeared to be slightly delayed in formation of the sporulation division septum compared to the parent strain.…”
Section: Insertion Of 23 Mbsupporting
confidence: 62%
See 1 more Smart Citation
“…3A). Engulfment was completed (stage III) within 60 to 90 min of septation, similar to times reported previously for B. subtilis (12,32). The strain containing the 2.3-Mb insert, SL14378, appeared to be slightly delayed in formation of the sporulation division septum compared to the parent strain.…”
Section: Insertion Of 23 Mbsupporting
confidence: 62%
“…Finally, the engulfing membranes fuse at the cell pole, releasing the completely engulfed prespore within the mother cell (stage III) (22,23). The time from septation to completion of engulfment is not known precisely; the best estimate is about 70 min at 37°C (12,32). Different studies indicate that chromosome replication is completed by stage IIi (2,18,21).…”
mentioning
confidence: 99%
“…The synthesis of new transcripts and average-size proteins can be achieved within 30 s, and the time taken for induction of a large protein such as ␤-galactosidase is about 2.5 to 3 min (30). However, more complex developmental adaptations such as sporulation take considerably longer (up to 7 to 8 h) (70). Likewise, biofilm formation can be observed within an hour, but mature biofilms can take Ͼ24 h (214).…”
Section: Introductionmentioning
confidence: 94%
“…An especially intriguing possibility is that ANTIBIOTICS INFLUENCE UE 4617 be the signal for the activation of acE. The coincidence of forespore septum formation (2) with the time at which the processing reaction occurs (30) suggested that formation of the septum is the putative morphological signal. It was hypothesized that the coupling of septum synthesis to sigma factor activation might be achieved by constructing the processing machinery as a part of the septum (11,16,25).…”
mentioning
confidence: 99%